2002
DOI: 10.7863/jum.2002.21.2.141
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Hepatic Hemangiomas With Levovist on Coded Harmonic Angiographic Ultrasonography

Abstract: Coded harmonic angiographic ultrasonography with a microbubble contrast agent can depict the typical enhancement pattern in most hepatic hemangiomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 17 publications
1
18
0
1
Order By: Relevance
“…To overcome the shortcomings of conventional harmonic imaging, various gray-scale harmonic imaging techniques have recently been developed (5, 7, 8, 11-13). Among these, digitally encoded harmonic US is the one that encodes the unwanted fundamental frequency component when transmitting pulses and then, through a decoding process when receiving signals, removes the pre-tagged fundamental echo without the loss of overlapping harmonic signals (14). The B-flow technique, optimized for direct visualization of blood cells at gray-scale imaging, uses codes to enhance weak blood echoes and equalize a non-moving tissue signal (15), and is thus free of Doppler artifact.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome the shortcomings of conventional harmonic imaging, various gray-scale harmonic imaging techniques have recently been developed (5, 7, 8, 11-13). Among these, digitally encoded harmonic US is the one that encodes the unwanted fundamental frequency component when transmitting pulses and then, through a decoding process when receiving signals, removes the pre-tagged fundamental echo without the loss of overlapping harmonic signals (14). The B-flow technique, optimized for direct visualization of blood cells at gray-scale imaging, uses codes to enhance weak blood echoes and equalize a non-moving tissue signal (15), and is thus free of Doppler artifact.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that lots of liver lesions show characteristic enhancement patterns on contrast-enhanced gray-scale ultrasonography. The most common enhancement pattern of hepatic hemangioma on contrast-enhanced harmonic US was peripheral globular enhancement with progressive centripetal fill-in (Kim et al, 2002;Ding et al, 2005). Centrifugal filling was the specific enhancement feature of focal nodular hyperplasia (Kim et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…CHA uses the B-flow technique, as well as digitally coded harmonic imaging. The B-flow technique, which is optimized for the direct visualization of blood cells on gray-scale images, uses codes to enhance weak blood echoes and equalize the non-moving tissue signal (19) Thus, the B-flow technique is free of Doppler-related artifacts. By combining the benefits of these two techniques, CHA allows the harmonic signals resulting from tissue to be separated from those arising from contrast agents, and boosts the harmonic return from the contrast agents, while suppressing not only the fundamental, but also the harmonic signals from the background tissue (18-20).…”
Section: Contrast-enhanced Usmentioning
confidence: 99%